Mesenchymal stem cells differentiate to retinal ganglion-like cells in rat glaucoma model induced by polystyrene microspheres - ERASLAN, MUHSİN; ÇERMAN, EREN; BOZKURT, SÜHEYLA; AKKOÇ, TUNÇ (My University, 2023)
Aim: The study aimed to evaluate the differentiation ability of intravitreally injected rat bone marrow-derived mesenchymal stem cells (rBM-MSCs) to retinal ganglion-like cells in a polystyrene microsphere induced rat glaucoma model. Materials and Methods: The glaucoma rat model was generated via intracameral injection of 7 microliter polystyrene microspheres. Green fluorescence protein-labeled (GFP) rBM-MSCs were transplanted intravitreally at or after induction of ocular hypertension (OHT), depending on the groups. By the end of the fourth week, flat-mount retinal dissection was performed, and labeled against Brn3a, CD90, GFAP, CD11b, Vimentin, and localization of GFP positive rBM-MSCs was used for evaluation through immunofluorescence staining and to count differentiated retinal cells by flow cytometry. From 34 male Wistar albino rats, 56 eyes were investigated. Results: Flow cytometry revealed significantly increased CD90 and Brn3a positive cells in glaucoma induced and with rBM-MSC injected groups compared to control(P = 0.006 and P = 0.003 respectively), sham-operated (P = 0.007 and P < 0.001 respectively), and only rBM-MSCs injected groups (P = 0.002 and P = 0.009 respectively). Immunofluorescence microscopy revealed differentiation of GFP labeled stem cells to various retinal cells, including ganglion-like cells. rBM-MSCs were observable in ganglion cells, inner and outer nuclear retinal layers in rBM-MSCs injected eyes. Conclusion: Intravitreally transplanted rBM-MSCs differentiated into retinal cells, including ganglion-like cells, which successfully created a glaucoma model damaged with polystyrene microspheres. Promisingly, MSCs may have a role in neuro-protection and neuro-regeneration treatment of glaucoma in the future.
Keywords: Tıp; Histoloji-Embriyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Mikrobiyal Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Histology and Embryology; Life Sciences; Molecular Biology and Genetics; Microbial Genetics; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); GELİŞİMSEL BİYOLOJİ; HÜCRE BİYOLOJİSİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; DEVELOPMENTAL BIOLOGY; CELL BIOLOGY; Gelişimsel Biyoloji; Hücre Biyolojisi; Developmental Biology; Cell Biology; Flow cytometry; Glaucoma; Microbead; Neuro-protection; Neuro-regeneration; Polystyrene microsphere; Retinal ganglion cell; Stem cell